Complete transition from open surgery to laparoscopy: 8‐year experience with more than 500 laparoscopic living donor hepatectomies. Issue 7 (5th June 2022) - Rhu, Jinsoo; Choi, Gyu‐Seong; Kim, Jong Man; Kwon, Choon Hyuck David; Joh, Jae‐Won
Abstract: This study was designed to review laparoscopic living donor liver transplantations (LDLTs) at a single center that achieved complete transition from open surgery to laparoscopy. LDLTs performed from January 2013 to July 2021 were reviewed. Comparisons between open and laparoscopic surgeries were performed according to periods divided into initial, transition, and complete transition periods. A total of 775 LDLTs, 506 laparoscopic and 269 open cases, were performed. Complete transition was achieved in 2020. Bile duct variations were significantly abundant in the open group both in the initial period (30.2% vs. 8.1%; p  < 0.001) and transition period (48.1% vs. 24.3%; p  < 0.001). Portal vein variation was more abundant in the open group only in the initial period (13.0% vs. 4.1%; p  = 0.03). Although the donor reoperation rate (0.0% vs. 4.1%; p  = 0.02) and Grade III or higher complication rate (5.6% vs. 13.5%; p  = 0.03) were significantly higher in the laparoscopy group in the initial period, there were no differences during the transition period as well as in overall cases. Median number of opioids required by the donor (three times [interquartile range, IQR, 1–6] vs. 1 time [IQR, 0–3]; p  < 0.001) was lower, and the median hospital stay (10 days [IQR, 8–12] vs. 8 days [IQR, 7–9]; p  < 0.001) was shorter in the laparoscopy group. Overall recipient bile leakage rate (23.8% vs. 12.8%; p  < 0.001) and overall Grade III or higher complication rate (44.6% vs. 37.2%; p  = 0.009) were significantly lower in the laparoscopy group. Complete transition to laparoscopic living donor hepatectomy was possible after accumulating a significant amount of experience. Because donor morbidity can be higher in the initial period, donor selection for favorable anatomy is required for both the donor and recipient.